Transcending gender and sex: ethical implications for identities, ambiguities and interrelations - Adenugba, Oluwaseun Adeola (Bangladesh Journal of Bioethics, 2012)
This paper examines the moral issues involved in the acts of transcending gender and sex. Attempts are made in answering such fundamental questions as: Is transgenderism necessary and beneficial? Does transsexualism necessarily imply transgenderism? Are natural rights violated by the acts of transcending sex and gender? What implications do development in trangenderism and transsexualism hold for our conventional linguistic resources, identity and interrelationships? Ought humans to be allowed freedom to choose to transcend gender and sex? What criteria should be used in avoiding bigotry against androgynous and in harmonizing relationships with their physician? We review the current state of clinical research with transsexualism and transgenderism, the history of transsexual research, the major moral arguments for and against the practices of transcending gender and sex, and the new ethical dilemmas sprawled as aftermath. The paper critically assesses the arguments on the dividing line of the debate. This paper establishes that the reasons offered for artificial intervention in traversing sex and gender are not sufficient and morally convincing enough. It concludes that instead of the predominant current attitude of aggressive intervention with naturally unique sexuality, together with its attendant discrimination and moral resentment against transsexuals and transgenders, it is more ideal to engage on the one hand, in an in-depth discussion with the concerned people, listen to their worries and see ways in which their problems could be addressed through counseling. An on the other hand, there is a need for public discourse and public awareness on the fluidity in gender and sexual orientation so that peoples attitude to this new development can be better sharpened. DOI: http://dx.doi.org/10.3329/bioethics.v3i1.10866 Bangladesh Journal of Bioethics 2012; 3(1):4-12